Razvoj pravosudnih vlasti i odgovarajućega pravnog okvira u Hrvatskoj 1945. godine The Development of Judicial Authorities and the Related Legal Framework in Croatia in 1945 - Grahek Ravančić, Martina (2021)
Organizacija i razvoj pravosudnih tijela i odgovarajućega pravnog okvira u Hrvatskoj nakon Drugoga svjetskog rata bila je nezaobilazna sastavnica ustrojavanja ukupne nove vlasti na ovim prostorima. Rad analizira okolnosti i uvjete u kojima se uspostavljaju sudski sustav (okružni i kotarski sudovi te "specijalni sudovi") i tužiteljstvo u Hrvatskoj te zadaci koji su stavljani pred poslijeratno sudstvo. Naglasak je stavljen i na pitanje zakonskoga kontinuiteta, koji je osim za osiguranje legaliteta iskorišten i u svrhu izgradnje i stabilizacije nove vlasti.
The organisation of the new government in the immediate aftermath of the war in Croatia encompassed and largely relied on the formation and development of judicial institutions and the accompanying legal regulations. This paper analyses the circumstances and conditions in which the judicial system was established and the tasks set before the post-war judiciary. It was essential to review how the regulations were standardised and how regular (circuit and district) courts and short-lived "special" courts, whose consequences were far-reaching, operated. It is important to highlight the significance of public prosecutors in Croatia. Through analysing archival sources and the available literature, an attempt was made to determine the extent that the legal vacuum that appeared after the severance of all ties with the pre-war laws made it easier to implement the new system, which sought to secure not only its own legality, but also the legitimacy of its authority.
Bibliografija
Summary.
Keywords: pravosuđe; sudovi; zakoni; javni tužitelj; Jugoslavija; Hrvatska; 1945.